Variations in diversity and distribution patterns of tree species under protected areas of Barak valley in the Eastern Indian Himalayas - Demsai Reang; Aparajita De; Ashesh Kumar Das (Geology, Ecology, and Landscapes)
Tropical forests are critical reservoirs of biodiversity yet remain among the most-threatened ecosystems. Protected areas (PA) play a vital role in conserving these forests and their rich biodiversity. The study assessed tree species diversity and conducted a comparative analysis across the three districts of Barak valley, Cachar (D1), Hailakandi (D2), and Karimganj (D3), Eastern Indian Himalayan region. 350 quadrats (10 m × 10 m) were randomly sampled within PA, documenting 194 tree species from 126 genera and 51 families. Species richness was highest under the PA of D1 (147), followed by D3 (99), and D2 (52). Tree basal cover showed identical trends, i.e. D1 (25.6 ± 0.49 m2 ha−1), D3 (22.7 ± 0.67 m2 ha−1) and D2 (20.2 ± 0.76 m2 ha−1). Biodiversity indices (Shannon, Margalef, Pielou, etc.) was highest for D1 than other districts, while stand density peaked in D3 (1798 ± 44 stems ha−1). The most dominant species include Artocarpus chama in D1 (IVI = 25.8) and D2 (IVI = 46.9), and Tectona grandis in D3 (IVI = 49). The presence of species listed under the IUCN Red List category includes vulnerable (n = 04), critically endangered (n = 02), endangered (n = 01), and near-threatened species (n = 01). The present study reveals the rich tree diversity within the PA of Barak valley, underscoring the need for district-specific forest conservation strategies to ensure long-term sustainability.